2007
DOI: 10.1242/dev.02854
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 is required for multipolar-to-bipolar transition during radial neuronal migration and proper dendrite development of pyramidal neurons in the cerebral cortex

Abstract: The mammalian cerebral cortex consists of six layers that are generated via coordinated neuronal migration during the embryonic period. Recent studies identified specific phases of radial migration of cortical neurons. After the final division, neurons transform from a multipolar to a bipolar shape within the subventricular zone-intermediate zone (SVZ-IZ) and then migrate along radial glial fibres. Mice lacking Cdk5 exhibit abnormal corticogenesis owing to neuronal migration defects. When we introduced GFP int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
154
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 155 publications
(173 citation statements)
references
References 46 publications
19
154
0
Order By: Relevance
“…It has been shown that the inability of cortical neurons to exit from the multipolar phase of radial migration results in abnormal dendritic development of pyramidal neurons in the postnatal cerebral cortex (21,22). Interestingly, previous studies revealed a role for TBC1D24 in neurite outgrowth in vitro (7,8,10), and we found that TBC1D24 expression also increased during postnatal development (Fig.…”
Section: Tbc1d24 Knockdown Alters Dendritic Arborization and Glutamatsupporting
confidence: 61%
See 1 more Smart Citation
“…It has been shown that the inability of cortical neurons to exit from the multipolar phase of radial migration results in abnormal dendritic development of pyramidal neurons in the postnatal cerebral cortex (21,22). Interestingly, previous studies revealed a role for TBC1D24 in neurite outgrowth in vitro (7,8,10), and we found that TBC1D24 expression also increased during postnatal development (Fig.…”
Section: Tbc1d24 Knockdown Alters Dendritic Arborization and Glutamatsupporting
confidence: 61%
“…Although this transitional phase requires a reorganization of the cytoskeleton, the molecular mechanism regulating this process has just begun to be dissected. Several microtubule regulators, such as LIS1, DCX, and CDK5, are essential for the exit of neurons from the multipolar stage (17,22,29), and accumulating evidence now indicates that membrane trafficking can also play a role in the morphological changes underlying radial migration of newborn neurons (30). Notably, Rab5-and Rab11-dependent endocytic pathways control multipolar transition and final CP positioning by regulating the surface expression of N-Cadherin in migrating neurons (30).…”
Section: Discussionmentioning
confidence: 99%
“…The newly generated neurons usually undergo transient multipolar transformation before assuming radial migration (8, 10). Based on these observations, it has been proposed that many developmental disorders, such as periventricular nodular heterotopia, subcortical band heterotopia, and doublecortex syndrome are related to migration abnormalities including its multipolar stage at SVZ/VZ (11-13).The molecular mechanisms controlling directly and/or indirectly the multipolar stage of neuronal migration have just begun to be recognized (7,(14)(15)(16)(17). For example, knockdown or inactivation of Filamin A or LIS1 accumulated the multipolar neurons in the VZ and SVZ, whereas knockdown or inactivation of Doublecortin (DCX) accumulated these cells in the IZ (18,19).…”
mentioning
confidence: 99%
“…All prospective cortical pyramidal neurons are generated in either the ventricular (VZ) or subventricular (SVZ) zones and, after their final division, migrate radially to the cortical plate (CP) situated beneath the pial surface (2). Although it has been observed long ago that cells in the SVZ and intermediate zone (IZ) display multiple processes as they choose and translocate between adjacent radial glial fibers (3,4), it has been only until recently possible to study this transient process by live imaging combined with genetic introduction of GFP (5)(6)(7)(8)(9). The newly generated neurons usually undergo transient multipolar transformation before assuming radial migration (8,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation